A LOVE FOR INDONESIA: THE YOUTH'S EFFORT IN INCREASING HONOR TOWARDS MUL TICUL TURALISM - Shieriy June; Ekawati Markaenny Dukut (Celt: A Journal of Culture, English Language Teaching & Literature, 2012)
Indonesia is a country which is full of cultures and diversities. A multicultural country usually finds and faces the same problem that is the internal conflicts and even separation. As the cultured humankind, people should see the diversity of cultures as the wealth of nations and the ancestor's heritage that should be well-kept and developed. This study is intended to discuss and analyze the multiculturalism in Indonesia, its development, and what the youth should do as the successor of the country to increase their honor towards multiculturalism as the writer sees that there are many youth who have lost their loyalty to their own cultures.